Analisis Fiqh Muamalah terhadap Praktik Jual Beli Online di Era Digital dengan Pembayaran Spaylatter - Muhammad Renaldi Aditya Putra; Eka Della Amel Nur Samsu; Ajeng Fitrianingrum; Auliya Dwiyanti; Luluk Afiatuz Zahro; Waluyo Waluyo (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Currently we have entered the era of digitalization or what is called the modern era. Technology is developing rapidly, especially in the field of online buying and selling that It makes it easier to access all the necessities of life. In Indonesia, there are many online sales and purchase applications, one of which is the Shopee application which provides various kinds of life needs ranging from food, clothes, household appliances and even tertiary needs (cars, motorcycles, and so on). Where shopee also provides various ways to pay, from on-site payment (COD system) when the goods are in the hands of the buyer, bank transfers, shopeepay transfers and even provides spaylater payments where this payment is made without having to pay immediately for the goods purchased or also called a credit system which of course is based on the terms and conditions that apply in the spaylater system. This research uses qualitative data, obtained from literature from various sources. The sources used are processed from the analysis of various journals, articles, reports and information related to the review of muamalah fiqh on the case of online purchases with credit system payments offered by Shopee through the "spaylater" feature.